Approaches for treating domestic wastewater with food waste and recovery of potential resources. Issue 1 (31st December 2022) - Giwa, Abdulmoseen Segun; Sheng, Mingqiang; Zhang, Xiaoqian; Wu, Yuanyuan; Bo, Huang; Memon, Abdul Ghaffar; Bai, Shuqin; Ali, Nasir; Ndungutse, Jean Maurice; Kaijun, Wang
ABSTRACT: Continuous population growth associated with sanitation, food waste (FW), and domestic wastewater (DWW) is becoming critical globally. Crucial efforts and appropriate measures to utilize the FW and DWW for resources are needed. This paper reviews the conventional treatment techniques, challenges, and associated merits for treating FW and DWW. In the context of this review, DWW is often referred to as blackwater (BW)/feces. Due to the rationale for resource amplification, the review proposed that both mixtures (FW and DWW) be stored in a sub-surface storage tank for several months or years. They are further biodegraded in a bioprocess to generate energy with stabilized digestates. The effluent's peculiar features are low organic acids with a low pH4 value, offering a stabilized and sanitized effluent. The second proposed route was to integrate anaerobic digestion, composting, and pyrolysis. Anaerobic digestion will offer bioenergy and digestates. Composting will cater to compost production and avert digestate drying and heating costs during pyrolysis. The pyrolysis of the digestates will generate biochar and bioenergy materials, while improved bioprocess performance is attained with the simultaneous biochar utilization in the bioprocess. The integrated technological routes can valorize DWW and FW for maximum resource recovery and sustainable development in a real-world context. The concept can be applied to an existing facility to create a cleaner and more efficient DWW with FW recycling. However, a comprehensive techno-economic analysis must be conducted.